(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
A robust adaptive backstepping sliding mode controller (ABSMC) is proposed for the speed regulation of a double-star induction machine (DSIM). This controller handles unknown or rapidly changing parameters while ensuring Lyapunov-based stability. First, a motor drive system model with lumped uncertainty is developed. Then, a nonlinear robust speed controller using the ABSMC theory is presented. In this technique, we employed to guarantee the speed tracking and parameter perturbation suppression. The simulation results indicate that the proposed control scheme effectively compensates for parameter perturbations while maintaining speed-tracking precision.